Multi-component reactions via copper(I) difluorocarbene as carbonyl source for constructing α—aminoamide derivatives - Jiuling Li; Baofan Wang; Taichen Liu; Qinghong Wen; Tongfei Jing; Xiang Fu; Yingming Pan; Kai Wei; Xiaoyu Zhou; Wenhao Hu; Zhenghui Kang (Nature Communications)
Abstract Difluorocarbene, an important reactive intermediate in organic synthesis, exhibits intriguing properties and synthetic versatility. However, great challenges in modulating reaction pathways limit its widespread application in synthetic chemistry. While metal-catalyzed difluorocarbene transfer offers a promising strategy but remains a formidable challenge. Herein, we disclose a copper-mediated multicomponent reaction of amine, aldehyde and BrCF2CO2K for synthesis of α- aminoamide derivatives, wherein copper-difluorocarbene serve as carbonyl source. Control experiments and DFT calculations support the pathway initiated by formation of a copper-difluorocarbene from BrCF2CO2K, followed by nucleophilic attack of the amine to produce an ammonium ylide, interception of the ylide with imine, and defluorination via carbonyl migration. This transformation demonstrates broad substrate scope, accommodating not only aromatic aldehydes but also alkyl aldehydes and drug-modified arylamines, highlighting its synthetic applicability. Furthermore, the method provides a practical and ideal alternative to classical Ugi or Strecker reactions, circumventing the need for toxic cyanide salts or unstable isonitriles.